Beam Weight Optimization on Radiotherapy Using Simulated Annealing Method - Ghassani Fikhrindita (NIM: 10211064), Shabrina
Radiotherapy is still an option to treat cancer both in the world and in Indonesia. Radiation using ionizing radiation is still being developed with variety of new ways and methods to make the therapy more effective and efficient. In general, therapy is done after the process of radiotherapy treatment planning (RTP), so that the therapy is given in accordance with the expected plan. As the time goes by, there are more supporting software used to perform RTP. In addition, there are also many emerging methods for the optimal therapy results. The optimum desired attainment is to maximize the dose absorbed by the cancer cells (targets) and to minimize the dose absorbed by organ at risk (OAR) and healthy tissue around the cancer cell. Many types of optimization are used to make the optimal therapy planning, one of them is beam weight optimization. Beam weight optimization is an optimation performed to give radiation weights to each angle beam used. It has to give the maximum dose for cancer cells (targets) and provide minimum doses for organ at risk and normal tissue around cancer cells. There are several methods to perform beam weight optimization. The simulated annealing is the method which will be used in this research. After doing beam weight optimization process using simulated annealing method, it is expected that the obtained results is better than the results before the optimization is done.